2016
DOI: 10.3389/fpls.2016.00348
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression between Leaf and Rhizome in Atractylodes lancea: A Comparative Transcriptome Analysis

Abstract: The rhizome of Atractylodes lancea is extensively used in the practice of Traditional Chinese Medicine because of its broad pharmacological activities. This study was designed to characterize the transcriptome profiling of the rhizome and leaf of Atractylodes lancea in an attempt to uncover the molecular mechanisms regulating rhizome formation and growth. Over 270 million clean reads were assembled into 92,366 unigenes, 58% of which are homologous with sequences in public protein databases (NR, Swiss-Prot, GO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 65 publications
0
23
1
Order By: Relevance
“…Previously, the de novo transcriptome was sequenced to produce the EST (comprehensive expressed sequence tag) dataset for Lycoris aurea , which provides one perspective of the regulatory and synthesized molecular mechanisms of Amaryllidaceae-type alkaloids (Wang et al, 2013). On the other hand, the inspection of the comparative transcriptome files between two databases provides another method to investigate the secondary metabolites biosynthesis, or/and find the objective genes involved in Salvia miltiorrhiza, Catharanthus roseus , sweet cherry, Atractylodes lancea , and so on (Guo et al, 2013; Yu and Luca, 2013; Wei et al, 2015; Huang et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Previously, the de novo transcriptome was sequenced to produce the EST (comprehensive expressed sequence tag) dataset for Lycoris aurea , which provides one perspective of the regulatory and synthesized molecular mechanisms of Amaryllidaceae-type alkaloids (Wang et al, 2013). On the other hand, the inspection of the comparative transcriptome files between two databases provides another method to investigate the secondary metabolites biosynthesis, or/and find the objective genes involved in Salvia miltiorrhiza, Catharanthus roseus , sweet cherry, Atractylodes lancea , and so on (Guo et al, 2013; Yu and Luca, 2013; Wei et al, 2015; Huang et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Despite the differences in the results of RNAseq and RT-qPCR, these methods have been widely used in many gene expression studies. Huang et al (2016) identified differential expressed genes (DEG) that regulate rhizome formation and development in Atractylodes lancea through comparative transcriptome analysis. Gene expression analysis of 20 selected genes was verified using RT-qPCR and all genes show similar trend of the expression patterns in the transcriptome analysis and the RT-qPCR (Huang et al, 2016).…”
Section: Tissue Specificity Analysis Of Xloc_10mentioning
confidence: 99%
“…Huang et al (2016) identified differential expressed genes (DEG) that regulate rhizome formation and development in Atractylodes lancea through comparative transcriptome analysis. Gene expression analysis of 20 selected genes was verified using RT-qPCR and all genes show similar trend of the expression patterns in the transcriptome analysis and the RT-qPCR (Huang et al, 2016). Similar method was used by Le Yu and his group, where the transcriptome data of Populus euphratica Oliv.…”
Section: Tissue Specificity Analysis Of Xloc_10mentioning
confidence: 99%
“…Recently, high-throughput RNA sequencing (RNA-seq) technology has become a powerful and costefficient means to facilitate an understanding of differential gene expression and regulatory mechanisms, especially for plant species without a reference genome [8,9]. RNA-seq has been widely used in the study of rhizome transcriptomics, including in various rhizomatous species such as sorghum (Sorghum halepense and Sorghum propinquum) [10,11], bamboo (Phyllostachys praecox) [12], Oryza longIstam-inata [13][14][15], Equisetum hyemale L. [16], Panax ginseng [17], reed (Phragm ites-australis) [18], tropical lotus (Nelumbo nucifera) [19], CangZhu (Atractylodes Lace-a) [20], Ligusticum chuanxiong [21], ginger (Zingiber officinale) [22], and Miscanthus lutarioriparius [8].…”
Section: Introductionmentioning
confidence: 99%